2019
DOI: 10.1152/ajpgi.00117.2019
|View full text |Cite
|
Sign up to set email alerts
|

Nod2 deficiency functionally impairs adaptation to short bowel syndrome via alterations of the epithelial barrier function

Abstract: Nucleotide-binding oligomerization domain-containing protein 2 ( NOD2) gene mutations are a risk factor for Crohn’s disease and also associated with worse outcome in short bowel syndrome (SBS) patients independent of the underlying disease. The aim of this study was to analyze the effect of Nod2 deficiency on barrier function and stool microbiome after extensive ileocecal resection in mice. Male C57BL6/J wild-type (WT) and Nod2-knockout (KO) mice underwent 40% ileocecal resection. Sham control mice received si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…We have previously reported that Nod2 k.o. animals develop very high plasma aldosterone concentrations in this SBS model [11]. In line with that, two upward outliers occurred only in the vehicle-treated Nod2 k.o.…”
Section: Teduglutide Improves Volume Statussupporting
confidence: 84%
See 4 more Smart Citations
“…We have previously reported that Nod2 k.o. animals develop very high plasma aldosterone concentrations in this SBS model [11]. In line with that, two upward outliers occurred only in the vehicle-treated Nod2 k.o.…”
Section: Teduglutide Improves Volume Statussupporting
confidence: 84%
“…1d), which suffer from less severe intestinal insufficiency than the Nod2 k.o. mice [11]. SBS-mediated body weight loss was significantly attenuated in the Teduglutide-treated wt animals (91.1 ± 1.8% wt Teduglutide vs. 84.1 ± 2.3% wt vehicle, day 14, Fig.…”
Section: Mice and Alleviates Intestinal Insufficiency In Wt Animalsmentioning
confidence: 85%
See 3 more Smart Citations